Socio-economic factors affecting the use of non-timber forest products in swine production in the Colombian Amazon - V. J. B. Martínez; Y. C. Medina; G. A. C. Parra (Journal of the Indonesian Tropical Animal Agriculture, 2022)
In view of the difficulties present in the swine production system to achieve sustainable productivity based on the comparative advantages and potential of the territory of the department of Caquetá, located in the natural region of the Colombian, the aim of the study was to analyze the socioeconomic factors that may influence the use of non-timber forest products (NTFPs) in live-stock feed. For this purpose, the study was carried out with a descriptive-transversal methodology with a non-experimental design and quantitative approach, where the survey was applied to 44 swine production units through a non-probabilistic method. The data were systematized using R software; a principal component analysis was performed and the degrees of relationship of socio-economic factors with the use of NTFPs in animal feed. It was concluded that despite being in a biodiverse territory, social factors related to the level of knowledge about NTFPs and economic factors linked to sources of financing are directly proportional to the degree of NTFP use in swine production in the department of Caquetá. Although NTFPs are found in most production systems in the region, they are not used for animal feed.